Maintenance of microclimate parameters in unheated parts of buildings by overflow air heating - S. V. Sarsyan; V. Yu. Kravchuk (Vestnik MGSU)
Introduction. Overflow air heating is a rarely used, but possessing a significant economic effect technology, the research of which is given insufficient attention. The subject of the research is the parameters of the thermal and humidity state of the air. The purpose of the research is to develop an algorithm describing the change of air state during the work of overflow air heating. Research objectives: to develop a model of air state change for overflow air heating; to apply the developed model and to formulate the recommendations on the organization of the overflow air heating for the warehouse building.Materials and methods. The research methodology is based on the traditional laws and equations of heat and mass transfer, aerodynamics and continuum mechanics; application of I–d diagram and the rules of construction of heat and humidity air treatment; principles of operation and design of ventilation equipment; sanitary and hygienic bases of ventilation design. Selection of climatic data, properties of materials, as well as the development of design solutions were carried out in accordance with the current regulatory documentation.Results. An algorithm including methods and models and describing the change in the state of the air for overflow air heating was developed. A model of air cooling in an unheated room was developed. It was tested on the example of a warehouse building with an unheated part. It confirmed the relevance of the developed model. Additionally, recommendations on the organization of optimal air distribution and selection of equipment were designed.Conclusions. The application of overflow air heating, calculated according to the proposed algorithm, will make it possible to increase the energy efficiency solutions in the field of ventilation of industrial buildings. The use of the algorithm implies that the organization of overflow air heating does not violate the technological process and requirements for fire and sanitary-hygienic safety of the building.